Madrasah Effort In Improving The Quality Of Teacher Work On Covid 19 Pandemic At Madrasah Aliyah Of Besitang - Wahyu Ziaulhaq (Nusantara Education, 2022)
This study describes the efforts of the head of the madrasa in maintaining the quality of teacher work during the covid-19 pandemic at the private preparatory madrasah aliyah in Besitang. The purpose of this research is to educate teachers always to evaluate the quality of teacher work so that the quality of work remains optimal in the mass of the covid 19 outbreak. This type of qualitative research seeks to explain social phenomena developing in the current mass. The data collection techniques he did were observation and unstructured interviews, then the data were analyzed objectively and then described scientifically by following the procedures for writing scientific papers using digital technology; give the task to the teacher to deliver material to students following the government's instructions. The principal of the madrasa conducts periodic supervision by monitoring learning activities online and the list of student assessments following student competence. The head of the madrasa seeks to improve coordination with parents of students related to the implementation of student learning activities while at home. The head of the madrasa continues to conduct Training for madrasa teachers so that madrasa teachers understand the procedures for making lesson plans and learning models by utilizing digital technology